Populist Mobilization Across Time and Space: An Introduction. Issue 4 (20th November 2017) - Bornschier, Simon
Abstract: Populism has become pervasive in political language and in the diagnosis of the malaise of contemporary politics. At the same time, more narrow definitions of populism have become shared in scholarship on the subject, nourishing more analytical approaches that put populism in historical and cross‐regional perspective. The purpose of this introduction is to use the evidence assembled in this special issue to ask some fundamental questions concerning the study of populist mobilization. Most importantly, what do we gain and what do we lose from sight by focusing on the commonalities between parties based on their populist appeals, when populist parties differ dramatically in terms of the substantive ideologies they adhere to? Are there distinctive features in terms of voter attitudes that underlie populist mobilization? And if failures of political representation and populism are intimately related, can we expect populists to render party systems more responsive to voters' substantive policy preferences?